Multivalent helix mimetics for PPI-inhibition - Barnard,A; Miles,JA; Burslem,GM; Barker,AM; Wilson,AJ (Organic & Biomolecular Chemistry, 2014)
The exploitation of multivalent ligands for the inhibition of protein–protein interactions has not yet been explored as a supramolecular design strategy. This is despite the fact that protein–protein interactions typically occur within the context of multi-protein complexes and frequently exploit avidity effects or co-operative binding interactions to achieve high affinity interactions. In this paper we describe preliminary studies on the use of a multivalent N-alkylated aromatic oligoamide helix mimetic for inhibition of p53/hDM2 and establish that protein dimerisation is promoted, rather than enhanced binding resulting from a higher effective concentration of the ligand.